Effects of fresh garlic extract on Candida albicans sessile cells, biofilms and biofilm associated genes, Flo-8 and Ndt80 - Thomas, Dave Aranka; Lee, Joshua, Voon Kai; Choo, Sulin; Rao, Harinash; Chong, Pei Pei (Life Sciences, Medicine and Biomedicine, 2022)
Candida-associated nosocomial infections are a persistent problem which has been steadily increasing over the years. The emergence of antimicrobial resistant strains has narrowed the spectrum of effective drugs that can be utilised and indicated the need for alternative therapeutics. Garlic is a spice often studied for its unique characteristics. Most of its antimicrobial properties have been attributed to the presence of allicin, which makes up more than 70% of thiosulfinates extracted from garlic. The present study aimed to determine the effects of fresh garlic extract (FGE) towards the expression of two major biofilm genes, Flo-8 and Ndt80 produced by C. albicans that enable the morphogenesis of yeast from planktonic cells to biofilm. Minimum concentration required for FGE to inhibit C. albicans was determined through agar well and disc diffusion assay. Effect of FGE towards preformed C. albicans biofilms was evaluated at ¼× and ½× inhibitory concentrations of FGE and Amphotericin B, respectively by XTT assay. RNA from FGE-treated C. albicans was extracted, reverse transcribed and analysed by Real-Time Polymerase Chain Reaction (RT-PCR) to determine FGE effects towards the expression of Flo-8 and Ndt80. Inhibitory concentration of FGE was determined to be 100 mg/mL. Both genes appeared to be upregulated in the presence of FGE with a higher upregulation noted with Flo-8 (67.34 and 30.20-folds) when compared against Ndt80 (5.55 and 1.79-folds) at 5 mg/mL and 10 mg/mL, respectively. It is surmised that C. albicans upregulated these genes as a survival mechanism in the presence of FGE. The findings from this study indicate that FGE could inhibit C. albicans growth and biofilms. Further research is required to determine the minimum inhibitory concentration (MIC) through broth microdilution and to understand the mechanism behind this phenomenon before it can be utilised as a potential therapeutic to combat Candida-associated nosocomial infections.